Circulating Levels of High Molecular Weight (HMW) Adiponectin and Total Adiponectin in Relation to Fat Distribution, Oxidative Stress and Inflammation in Asian Indians. Issue 4 (21st May 2013) - Indulekha, K.; Surendar, J.; Anjana, R.M.; Gokulakrishnan, K.; Balasubramanyam, M.; Aravindhan, V.; Mohan, V.
Abstract : Aim : To look at the association of total and high molecular weight (HMW) adiponectin with markers of fat distribution, oxidative stress and inflammation in Asian Indians. Methods : A total of 120 subjects were chosen randomly from Chennai Urban Rural Epidemiological Study. Fasting HMW adiponectin levels, TNF-alpha and oxidized LDL were measured using ELISA. High sensitivity C reactive protein (hsCRP) was measured by a high sensitive nephelometric assay. Lipid peroxidation was measured by Tbars assay and protein carbonyl content was assessed by DNPH assay. Visceral and subcutaneous fat areas were assessed by computed tomography (CT) scan. When stratified based on the tertiles of visceral fat, the levels of total ( p = 0.03) and HMW adiponectin ( p = 0.007) were highest in the first tertile followed by tertiles 2 and 3 whereas in tertiles of subcutaneous fat, there was no such trend. With increasing tertiles of Tbars, the levels of total ( p = 0.03) and HMW adiponectin decreased ( p = 0.002). The levels of HMW ( p < 0.001) but not total adiponectin was also found to decrease with increasing tertiles of Protein carbonyl content. The levels of Total ( p = 0.02) and HMW adiponectin ( p = 0.004) were highest in the first tertile of oxidized LDL followed by tertile 2 and tertile 3. With increasing tertiles of TNF-alpha total ( p = 0.01) and HMW adiponectin ( p = 0.004) was found to decrease. With increasing tertiles of hs-CRP, Total ( p = 0.005) and HMWadiponectin ( p = 0.007)was found to decrease. Conclusion : Oxidative stress markers, visceral but not subcutaneous fat and inflammation are associated with total and HMW adiponectin levles in Asian Indians.